Islamic Political Thought and Cultural Revival in Modern Indonesia - M. Din Syamsuddin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Views of Islamic political thought, at least there are three currents of thought among Indonesian Muslim intellectuals; formalistic currents, currents substantivistik, and fundamentalist currents. One view of current formalistic, he said Islam is a universal religion and overall (total). He emphasized the power of God on earth and as the views of Islamic fundamentalism, the danger of